2000
DOI: 10.1021/jf990866s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lactic Acid on the Solubilization of Protein during Corn Steeping

Abstract: The role of lactic acid (LA) in corn wet-mill steeping is not well understood. Because LA is known to improve wet-milling starch yields and steepwater contains a large amount of proteinaceous material, one of the effects of LA in steeping may be to help break down the endosperm protein matrix. Protein solubilization was studied for four different steeping solutions containing LA, sulfur dioxide (SO(2)), a combination of LA and SO(2), or no added chemicals at temperatures between 44 and 60 degrees C with steep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
25
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 13 publications
7
25
0
Order By: Relevance
“…It has been reported previously that much of the waterand saline-soluble proteins are lost during the steeping step of wet-milling [2,23]. The actions of lactic acid and, to some degree, SO 2 cause alterations and breakdown of the protein structure, resulting in the solubilization of fractions that are extracted, mainly from the germ, into the different product streams [23,24]. Parris et al [25] reported that the amounts of albumins and globulins were significantly less in commercial wet-milled corn germ (25% combined total) compared with that in corn kernel embryo (71%) and commercial dry-milled germ (72%).…”
Section: Protein Extraction Efficienciesmentioning
confidence: 99%
“…It has been reported previously that much of the waterand saline-soluble proteins are lost during the steeping step of wet-milling [2,23]. The actions of lactic acid and, to some degree, SO 2 cause alterations and breakdown of the protein structure, resulting in the solubilization of fractions that are extracted, mainly from the germ, into the different product streams [23,24]. Parris et al [25] reported that the amounts of albumins and globulins were significantly less in commercial wet-milled corn germ (25% combined total) compared with that in corn kernel embryo (71%) and commercial dry-milled germ (72%).…”
Section: Protein Extraction Efficienciesmentioning
confidence: 99%
“…Our initial experiments using a single yellow dent hybrid showed that there was a substantial increase in steepwater nitrogen (protein) when LA was added to batch steeps (Dailey et al 2000). Since the findings for one hybrid could have been atypical, steeping studies have been performed on an additional seven hybrids to evaluate the effect across a range of corn hybrids.…”
mentioning
confidence: 99%
“…41 Addition of SO 2 and lactic acid enables breakage of cross-linking disulfide bonds in the endosperm protein matrix, 22,23 and possibly of the recombinant protein as well. In the case of LT-B and of most proteins, correct folding and functionality depends highly on disulfide bond formation.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous findings 27 where lactic acid and sulfite treatment result in loss of biological activity of proteins, probably due to denaturing. 22 In this sense, the data are useful for future studies in which specific objectives want to be met regarding total LT-B yield or high concentration factors in particular fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation